PROSPECTIVE MICRO AND SMALL ENTERPRISES (MSES) IN BALIKPAPAN - Sugianto Sugianto; Casmudi Casmudi; Setyana Tungga Dewi; Linda Ayuni; Dianita Aprilia; Cantika Regina; Deswa Nuralya; Yunita Presitini (SEAN Institute, 2023)
The background of Micro Small Enterprises (MSEs) is currently contracting. Not yet recovered from the devastating Covid-19 pandemic, most business units have almost closed. Entering 2022, business actors are faced with a situation of uncertainty due to the war between Russia and Ukraine has not yet been resolved. Business climate conditions are increasingly shocking, overshadowed by the global economic recession in 2023. Some local MSE actors take it seriously, but some are normal. The objectives of the study (1) describe the perspective aspects of organizing micro and small enterprises (MSEs), (2) present the position of MSEs in Balikpapan to welcome the development of the Capital City of the Archipelago (IKN) (3) Reveal the strategy of MSEs to welcome the development of IKN. This qualitative discretive research took the MSE segment in Balikpapan. Samples of 6 types of businesses (1) Restaurant, (2) Café, (3) Beverage, (4) Hydroponics, (5) Seafood, (6) Tofu and Tempeh Industry. Data collection using observation, structured interviews, data collection assisted by 5 groups by conducting internships for 7 days. The position of the researcher as supervisor 1 and 2. The results of the study achieved very good category scores (81-100) (1) Hydroponics and Seafood 97 Percent (2) Restaurants and Cafes 93 percent (3) Beverages 95 Percent and Tofu Tempeh 90 Percent. There are 11 indicators, namely (1) Character of business actors (2) Business planning, (3) Market and marketing, (4) Production operations, (5) Business location, (6) Organization management, (7) Marketing mix, (8) Business competition, (9) Market confidence, (10) Financial management and (11) Business feasibility. The conclusion of the study to six Micro and Small Enterprises (MSEs) business units in Balikpapan has very good prospects, the lowest achievement score of 90 percent and the highest of 97 percent.